Design Principles for Integration of Model-Driven Quality Assurance Tools - Crelier, Othon; Silva Filho, Roberto S.; Hasling, William M.; Budnik, Christof J. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
The engineering of software systems is supported by tools in different phases of the software development. The integration of these tools is crucial to assure the trace ability of existing models and artifacts, and to support the automation of critical software development phases such as software testing and validation. In particular, the integration of novel software quality assurance tools into existing environments must be performed in a way that minimizes its impact on existing software process, while the benefits of the tool are leveraged. This guarantees the adoption of new methodologies with minimal interference in existing production workflow. In this paper we discuss our experience in integrating a model-driven software testing tool developed within SIEMENS with a widely-adopted model-driven design tool. In particular, we establish a set of design principles from the lessons learned in this integration. We conclude showing a design that prioritizes data integration over control and presentation that achieves a high degree of tool integration while minimizing the integration development effort.